Influence of Students’ Family Backgrounds on Management of Their Discipline in Public Secondary Schools In Kenyenya Sub County, Kisii County, Kenya - Tabitha Mogonchi; Christopher Makworo Ayienda (IJRDO- Journal of Educational Research, 2020)
School discipline is a matter of concern particularly among teachers, family, educators and other stakeholders. Students cannot learn and teachers cannot teach effectively in an undisciplined and unsafe environment and therefore order and discipline are necessary for successful educational outcomes. The purpose of this study was to establish the influence of students’ family background on management of discipline in public secondary schools in Kenyenya Sub County, Kisii County, Kenya. The study was guided by the Social Learning Theory and System Management Theories. The study adopted a concurrent triangulation design with a mixed design methodology where both qualitative and quantitative methods were employed. The study population were all the public secondary schools in Kenyenya Sub County, Kisii County including all the students, teachers and deputy principals. All 30 secondary schools were purposively sampled as well as all 30 deputy principals as well as all 30 teachers in charge of guidance and counseling in these schools. A stratified random sampling method was used to pick 379 students. Purposive sampling was used to pick 30 deputy principals and 30 teachers in charge of discipline management. Questionnaires and interview schedules were used in data collection. The study was piloted in 5 schools in the neighbouring Keroka Sub County. Reliability and validity of the research instruments were tested during piloting as well as taking into consideration 2 experts’ assessments respectively. Statistical Package for Social Sciences (SPSS) was used in data analysis to generate the frequencies, descriptive statistics, cross-tabulation statistics, chi-square tests as well as correlation coefficient statistics that were used to analyze the data and answer the research questions. Findings were presented using statistical tables. The study made some important findings that drew it to make some important conclusions. It can be noted that there were significant relationships between school characteristics and issues of indiscipline. The following recommendations were made; school rules and regulations need to be emphasized and given enough awareness so as to enable students understand them. These will help to prescribe the standard of behavior expected of students and teachers. Students will learn to behave like students and so will be the teachers. Deputy Principals should design proper ways of handling punishments. Disciplinary committees therefore need to be installed in schools that they are not in existence and to be respected in terms of decision-making and be given powers and authority to execute their duties. The school administration needs to come up with timetables or regular time intervals to need to provide time for counseling and guidance to students so as to prevent occurrence of offences than punishing the offenders.